Excess serum Na level in rats administered with high doses of (−)-epigallocatechin gallate-casein nanoparticles prepared with sodium caseinate. Issue 3 (14th January 2022) - Zhang, Yahui; Han, Shuya; Wang, Yin; Zhang, Haihua; Yu, Chenhuan; Qin, Dingkui; Du, Qizhen; Jin, Peng
Abstract : The 28-day oral toxicity test of 5.0 g per kg BW FD-EGCG-NPs on rats did not show any adverse effect. However, Na level in the serum of females and males treated with 10.0 g per kg BW FD-EGCG-NPs or FD-NPs significantly increased ( P < 0.05). Abstract : (−)-Epigallocatechin gallate (EGCG)-incorporated casein nanoparticles benefit from excellent antioxidant, anti-inflammatory and anti-cancer activities due to their synergistic efficiency, but few studies have evaluated their safety. In this study, the EGCG-casein nanoparticles (EGCG-NPs) formulated using caseinate by ultrasonic treatment were evaluated for their subacute toxicity. The subacute toxicity test of EGCG-NPs through 28-day oral administration in rats did not exhibit adverse effect, with a no-observed-adverse-effect level (NOAEL) of at least 5.0 g per kg body weight (BW) per day, which was equivalent to 500 mg per kg BW EGCG per day. However, the serum Na level in females and males treated with 10.0 g per kg BW EGCG-NPs increased significantly as compared to the control rats ( P < 0.05). Similar indications appeared in rats treated with 10.0 g per kg BW pure casein nanoparticles without EGCG, which indicated that high doses of caseinate nanoparticles result in an excess serum Na level. Therefore, we should consider the safety of the nanoparticle formulation of caseinate when it is used as a loading nutrient and a functional substance in foods.